Management Of Teacher Performance Appraisal In Improving The Quality Of Madrasah Learning - Alfaiz, Baraz Yoechva; Mudofir, Mudofir; Hikmawati, Sabar Indah; Suppriyadi, Suppriyadi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
The purpose of this paper is to describe the dimensions and indicators of teacher performance and analyze the impact of teacher performance indicators on the quality of madrasah education. Based on the results of research that has been done the method used is qualitative. So it can be concluded that teacher performance is the result of the work, progress, and efficiency of teachers in the implementation of education, both planning and implementing the educational process, assessing learning outcomes, directing and training students, as well as fulfilling tasks in carrying out their duties. Whether or not a teacher's performance is good is determined by the application of competencies that a teacher must have in addition to good academic qualifications. Efforts to improve the quality of education have become a national strategic issue as well as a study of education quality management. The teacher performance factor is one of the factors that determine the efficiency of a madrasah in following educational standards. The professional size and personality of teachers have a strong influence on improving the achievement of madrasah quality standards. The results obtained show that good teacher performance and teacher academic qualifications affect the quality of education. These results show that the positive impact of teacher performance and teachers' academic qualifications is an important variable in efforts to improve the quality of education. Keywords: Assessment Management, Teacher Performance, Academic Quality Improvement